2009
DOI: 10.1016/j.schres.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

NPY mRNA expression in the prefrontal cortex: Selective reduction in the superficial white matter of subjects with schizoaffective disorder

Abstract: Background-Alterations in the inhibitory circuitry of the dorsolateral prefrontal cortex (DLPFC) in schizophrenia include reduced expression of the messenger RNA (mRNA) for somatostatin (SST), a neuropeptide present in a subpopulation of γ-aminobutyric acid (GABA) neurons. Neuropeptide Y (NPY) is expressed in a subset of SST-containing interneurons and lower levels of NPY mRNA have also been reported in schizophrenia spectrum disorders. However, whether the alterations in these two transcripts identify the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…This increased colocalisation of these markers in the disease state, may be paralleled with changes of SST+ cells, although quantification remains to be carried out. It should be noted that in a previous report, density of NPY+ IWMNs was unaltered in schizophrenia subjects (42), although a decrease of NPY+ IWMNs was noted in schizoaffective subjects suggesting that the NPY+ IWMN subpopulation may be susceptible in a particular diagnostic type of schizophrenia.…”
Section: Discussionmentioning
confidence: 56%
“…This increased colocalisation of these markers in the disease state, may be paralleled with changes of SST+ cells, although quantification remains to be carried out. It should be noted that in a previous report, density of NPY+ IWMNs was unaltered in schizophrenia subjects (42), although a decrease of NPY+ IWMNs was noted in schizoaffective subjects suggesting that the NPY+ IWMN subpopulation may be susceptible in a particular diagnostic type of schizophrenia.…”
Section: Discussionmentioning
confidence: 56%
“…However, the sample size in some of these studies may not have had sufficient power to detect a difference. Interestingly, a small number of studies have reported molecular or cellular differences in PFC between these two diagnoses: 1) lower expression of arrestin and G-protein coupled receptor kinases was found selectively in schizophrenia subjects (74), 2) lower expression of neuropeptide Y mRNA was found selectively in the white matter of schizoaffective disorder subjects (75), and 3) a laminar-specific increased density of pyramidal cells and decreased density of putative interneurons was found selectively in schizoaffective disorder subjects (76). Thus, in concert with the current study, the existing postmortem literature provides some support for the disease process of schizoaffective disorder as having both distinct differences and substantial similarities with the disease process operative in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the GABAergic neurons in the subcortical white matter are affected in psychosis, though these alterations differ from those observed for MAP2 and NeuN‐immunoreactive neurons; specifically, alterations within the GABAergic cell population appear to be molecular in nature rather than an overt change in cell number or density. For example, the mRNA for NPY, which is expressed by many NOS1/NADPH‐d neurons mentioned above (Suarez‐Sola et al, 2009), is selectively decreased in neurons within superficial white matter of subjects with psychosis, particularly in cases with prominent mood symptoms (Morris et al, 2009). Similarly, the RELN transcript for the glycoprotein Reelin—which is expressed by GABAergic neurons (Guidotti et al, 2000)—was significantly lower in WMN in schizophrenia (Eastwood and Harrison, 2003, 2006).…”
Section: Which Subpopulations Of Wmn Are Altered In Schizophrenia?mentioning
confidence: 99%
“…While nitric oxide, produced by NOS1, facilitates blood flow through the cortical microvasculature, NPY mediates microvessel constriction (Cauli et al, 2004). Therefore, any alterations in gene expression or spatial distribution of these subpopulations of WMN (Akbarian et al, 1993a; Eastwood and Harrison, 2003; Morris et al, 2009) may seriously impair the proper regulation of cerebral blood flow and metabolism. This hypothesis is consistent with in vivo neuroimaging studies reporting functional hypoactivity in cerebral cortex in schizophrenia, as assessed by Blood‐Oxygen‐Level‐Dependent (BOLD) and functional magnetic resonance imaging (fMRI) (Potkin and Ford, 2009; Fu and McGuire, 1999; Sava and Yurgelun‐Todd, 2008).…”
Section: Implications Of White Matter Neuron Changes For the Pathophymentioning
confidence: 99%